TRADISI MACCÈRAK PÃREK SEBAGAI BENTUK KEARIFAN LOKAL MASYARAKAT SUKU BUGIS DI TANJUNG JABUNG TIMUR JAMBI - Haeran Haeran (Sabda: Jurnal Kajian Kebudayaan, 2019)
Each society or territory has culture and its characteristics. One of them is Bugisness society in the region of East Tanjung Jabung whose maccérak pãrek tradition, a tradition which combines tradition and religion. Data were collected by interviewing, document study, and direct observation, then analyzed by using descriptive qualitative method. The result of the study found that the Bugisness society in East Tanjung Jabung as outsiders, always keep their anchestors’ tradition that was inherited from generation to generation, which is implemented into maccérak pãrek tradition, a tradition as manifestation of thanksgiving to God and respecting to supranatural creatures who are given power by God to keep a place or territory in social harmony. The implementation of this tradition beginning with preparation phase, slaughtering phase and, ended by, implementation phase. The impact of this tradition is expected to weave harmonious relationship of society, government and environment. The values of harmonious cooperation can also be found in the implementation of this local wisdom.. The implementation of values of this tradition is not only to build harmony in Bugisness society, but also between Bugisness and other etnic groups.